2020
DOI: 10.1111/jan.14584
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative systematic review: Sources of inaccuracy in manually measured adult respiratory rate data

Abstract: Aims To identify the potential sources of inaccuracy in manually measured adult respiratory rate (RR) data and quantify their effects. Design Quantitative systematic review with meta‐analyses where appropriate. Data Sources Medline, CINAHL, and Cochrane Library (from database inception to 31 July 2019). Review Methods Studies presenting data on individual sources of inaccuracy in the manual measurement of adult RR were analysed, assessed for quality, and grouped according to the source of inaccuracy investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 92 publications
2
16
0
Order By: Relevance
“…This suggests that a significant amount of heterogeneity is related to the reference standard. For example, studies which employed manual counting as a reference standard tended to be more heterogeneous, in keeping with previous studies documenting their unreliability [81].…”
Section: Discussionsupporting
confidence: 70%
“…This suggests that a significant amount of heterogeneity is related to the reference standard. For example, studies which employed manual counting as a reference standard tended to be more heterogeneous, in keeping with previous studies documenting their unreliability [81].…”
Section: Discussionsupporting
confidence: 70%
“…Fever and respiratory symptoms are the two most common presentations of patients with COVID-19 [ 53 , 54 , 55 ], and patients with such symptoms also exhibit an additional risk of sepsis change and respiratory failure [ 56 , 57 ]. Although some studies [ 58 , 59 ] indicated respiratory rate was not precisely measured in most conditions, we considered a cutoff of respiratory rate of >22 should be easily assessed by the well-trained nurses and physicians. Other risk scoring tools for assessment of the degree of illness of patient, including the National Early Warning Score (NEWS) [ 60 ] and the Modified Early Warning Score (MEWS) [ 60 , 61 ], include the respiratory rate as an essential component.…”
Section: Discussionmentioning
confidence: 99%
“…Recorded measured vital parameters may be subject to some uncertainty [ 33 ], especially SpO2 is dependent on the patient's peripheral perfusion, and the blood pressure measurement can vary greatly when taken in a moving vehicle. Counting the respiratory rate is probably rarely done conscientiously over one minute, but rather estimated with consequent misjudgments [ 34 ]. Automatic registration of respiratory rate using EtCO 2 measurement or ECG monitoring in the prehospital setting, with the current technology applied is practically useless, as it is extremely sensitive to the patient moving, talking, coughing, or being in a moving vehicle etc.…”
Section: Discussionmentioning
confidence: 99%